2002
DOI: 10.1002/jnr.10171
|View full text |Cite
|
Sign up to set email alerts
|

DNA microarray analysis of the contused spinal cord: Effect of NMDA receptor inhibition

Abstract: Spinal cord injury (SCI)-induced neurodegeneration leads to irreversible and devastating motor and sensory dysfunction. Post-traumatic outcomes are determined by events occurring during the first 24 hours after SCI. An increase in extracellular glutamate concentration to neurotoxic levels is one of the earliest events after SCI. We used Affymetrix DNA oligonucleotide microarrays (with 1,322 DNA probes) analysis to measure gene expression in order to test the hypothesis that SCI-induced N-methyl-D-aspartate (NM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 68 publications
2
74
0
Order By: Relevance
“…The pattern of transcript expression was highly orchestrated from 1 to 90 d after injury and consistent in two distinct rat strains. As seen with thoracic contusions (Carmel et al, 2001;Song et al, 2001;Nesic et al, 2002;Tachibana et al, 2002;Di Giovanni et al, 2003;Pan et al, 2004), a profound loss of neural gene expression was observed by 1 d post-SCI. In our longitudinal study, a very modest rebound occurred by 90 d postinjury, reflective of neural tissue loss within the lesion.…”
Section: Discussionmentioning
confidence: 98%
“…The pattern of transcript expression was highly orchestrated from 1 to 90 d after injury and consistent in two distinct rat strains. As seen with thoracic contusions (Carmel et al, 2001;Song et al, 2001;Nesic et al, 2002;Tachibana et al, 2002;Di Giovanni et al, 2003;Pan et al, 2004), a profound loss of neural gene expression was observed by 1 d post-SCI. In our longitudinal study, a very modest rebound occurred by 90 d postinjury, reflective of neural tissue loss within the lesion.…”
Section: Discussionmentioning
confidence: 98%
“…To overcome this caveat we employed fairly rigid standards of present vs. absent conditions in the analyses of the microarray analyses as described in MATERIALS AND METHODS. For the RPA analyses, the lower threshold of sensitivity is in the picogram range, whereas for the microarray analyses, although it is hard to determine based on our experience in a number of paradigms (20), it is more in the nanomolar range.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the nuclear factor-B (NF-B) family of transcription factors is an especially signifi cant event considering the fact that NF-B is a critical step in the inducible regulation of over 150 genes involved in infl ammatory, proliferative and cell death responses [41] . A comprehensive analysis of the molecular events following spinal cord injury using DNA microarray analysis has shown that 1 h after trauma there are changes in mRNA levels for 165 genes [42] . In this analysis, SCI affected mRNA levels of genes that regulate transcription factors, infl ammatory processes, cell survival, and membrane excitability.…”
Section: Secondary Injury Cascade Following Spinal Cord Injurymentioning
confidence: 99%